Proceedings of SPE/IADC Drilling Conference 2007
DOI: 10.2523/105792-ms
|View full text |Cite
|
Sign up to set email alerts
|

More Ultradeepwater Drilling Problems

Abstract: TX 75083-3836 U.S.A., fax 1.972.952.9435. AbstractA 1999 SPE/IADC paper (52782) identified and documented solutions to a number of drilling problems encountered in Ultra-deepwater drilling. Since that time the industry has pushed the water depth record beyond 10,000' of water and drilling depths below 32,000'. A number of new problems have occurred in the last 8 years that have been caused by mechanical failures (equipment stressed to its limits) or human error. In the Gulf of Mexico recent drilling has encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…UD waters are characterized by high pressure, high temperature (HPHT) zones, gas pockets, and increasing amount of hydrogen sulphide (H 2 S), with associated reliability problems such as infant mortality, depth/pressure sensitivity, environmental corrosion/erosion, salt water ingress and design performance failures [9]. According to [10], problems associated with the increase in water depth include: weather problems, mechanical failures of subsea equipment, wellbore instability, formation and cementing issues and specifically, BOP challenges. Blowout control in these new environments has not been mastered and is often handled reactively.…”
Section: Deep and Shallow Watersmentioning
confidence: 99%
See 1 more Smart Citation
“…UD waters are characterized by high pressure, high temperature (HPHT) zones, gas pockets, and increasing amount of hydrogen sulphide (H 2 S), with associated reliability problems such as infant mortality, depth/pressure sensitivity, environmental corrosion/erosion, salt water ingress and design performance failures [9]. According to [10], problems associated with the increase in water depth include: weather problems, mechanical failures of subsea equipment, wellbore instability, formation and cementing issues and specifically, BOP challenges. Blowout control in these new environments has not been mastered and is often handled reactively.…”
Section: Deep and Shallow Watersmentioning
confidence: 99%
“…-Shearing capabilities Blind and casing shear ram preventers are fitted with blades, to cut through different tubing types, and seal off a well. Failure to shear is not very common [10]. However, as drilling advances into UD waters, drill pipe properties such as material strength, toughness and ductility are continuously improved to reduce drill pipe failure and increase life span, which result in increased shearing force requirements.…”
Section: Design Challenges -Sealing Elementsmentioning
confidence: 99%
“…Affected by the drilling vessel drifting and sea current beating and other issues, the riser would threaten the stability of subsea wellhead mechanics [4][5][6][7]. Recent years scholars have conducted relational studies such as riser stress state, the stability of subsea wellheads, the bearing capacity of casing string below the mud line, the setting depth of conductor and so on, they have drawn some valuable conclusions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…IADC identified that the casing riser and conductor analysis should be conducted in a coupled manner [2]. As the loads on the bottom of the riser will be transferred to the wellhead and conductor, the coupled concept of riser and conductor is concerned [11]. King et al (1993) developed a new approach to analyze the behavior of a drilling riser and conductor as a complete entity, and the FEM was used in his research [12].…”
Section: Introductionmentioning
confidence: 99%